Above the waterfall : a novel - Rash, Ron, 1953- (HarperCollins, 2015)
Enduring the mistakes and tragedies that have shaped their lives in contemporary Appalachia, a sheriff on the brink of retirement and a haunted park ranger confront violent forces when an elderly local is accused of poisoning a trout stream.